Perovskite solar cells: A brief review on structural evolution and fabrication techniques - Ho Phuong (Journal of Technical Education Science, 2020)
Solar energy is regarded as one of the most promising renewable energy sources for future green technology. Solar energy can be directly converted into electricity by electrical devices called solar cells through photovoltaic effect. Intensive research works have been done in the photovoltaic field since the first solar cell was fabricated in 1954, leading to the formation of various kinds of solar cells. Among those, Perovskite solar cells (PSCs) have received great attention from researchers in recent years due to their outstanding performance. Since the first Perovskite solar cell was introduced, research in this area has intensively increased resulting in a rapid increment in power conversion efficiency of devices from 3.8% in 2009 to 25.2% in 2020. PSCs have become competitive candidates in the photovoltaic market to replace traditional Silicon solar cells. This article provides a brief review on structural progress of PSCs and the development in fabrication methods. The remaining challenges for long-term stability of PSCs are also addressed.